Economic, Fiscal, and Monetary Policy Uncertainty in Japan: What do They Affect? - Gessie Louis (European Scientific Journal, ESJ, 2025)
This paper examines how economic, fiscal, and monetary policy uncertainty shape Japan’s macroeconomic and financial conditions from 2004 to 2024. Using a VAR framework that includes economic policy uncertainty (EPU), fiscal policy uncertainty (FPU), and monetary policy uncertainty (MPU), we study their effects on money-supply growth, industrial production, inflation, and stock-market returns. We complement this analysis with GARCH-type volatility models to evaluate whether uncertainty meaningfully increases financial-market volatility. The results show that EPU has a consistent and significant impact on money-supply growth and industrial production, while inflation responds only weakly and gradually. Stock-market reactions are short-lived and show no strong evidence of heightened volatility. FPU and MPU play a secondary role: they appear in the VAR system but exert weaker and less stable effects on macroeconomic outcomes. Robustness checks, including alternative VAR lag structures, Granger causality tests, and additional volatility regressions, confirm the stability of these findings. The evidence suggests that Japan’s institutional setting, particularly the Bank of Japan’s communication strategy and policy tools, helps limit the transmission of uncertainty to asset-market volatility. These results highlight the importance of transparent and well-coordinated fiscal and monetary policies during periods of elevated uncertainty.